Association of a 4-tiered classification of left ventricular hypertrophy with adverse cardiovascular outcomes in the general population - Garg, Sonia (JACC Cardiovasc Imaging, 2015)
OBJECTIVES: This study was performed to determine whether a 4-tiered classification of left ventricular hypertrophy (LVH) defines subgroups in the general population which are at variable risk of adverse cardiovascular outcomes. BACKGROUND: We recently proposed a 4-tiered classification of LVH where eccentric LVH is subdivided into “indeterminate hypertrophy” and “dilated hypertrophy” and concentric LVH into “thick hypertrophy” and “both thick and dilated hypertrophy,” based on the presence of increased left ventricular end-diastolic volume. METHODS: Participants from the Dallas Heart study who underwent cardiac magnetic resonance imaging and did not have LV dysfunction or history of heart failure (HF) (n = 2,458) were followed for a median of 9 years for the primary outcome of HF or cardiovascular (CV) death. Multivariable Cox proportional hazard models were used to adjust for age, sex, African-American race, hypertension, diabetes, and history of cardiovascular disease (CVD). RESULTS: In the cohort, 70% had no LVH, 404 (16%) had indeterminate hypertrophy, 30 (1%) had dilated hypertrophy, 289 (12%) had thick hypertrophy, and 7 (0.2%) had both thick and dilated hypertrophy. The cumulative incidence of HF or CV death was 2% with no LVH, 1.7% with indeterminate, 16.7% with dilated, 11.1% with thick, and 42.9% with both thick and dilated hypertrophy (log rank p< 0.0001). Compared with participants without LVH, those with dilated (HR 7.3, 95% CI 2.8–18.8), thick (HR 2.4, 95% CI 1.4–4.0), and both thick and dilated (HR 5.8, 95% CI 1.7–19.5) hypertrophy remained at increased risk for HF or CV death after multivariable adjustment, whereas the group with indeterminate hypertrophy was not (HR 0.9, 95% CI 0.4–2.2). CONCLUSION: In the general population, the 4-tiered classification system for LVH stratified LVH into subgroups with differential risk of adverse CV outcomes. Unstructured Abstract: Participants from the Dallas Heart Study were stratified using a 4-tiered classification of left ventricular hypertrophy (LVH) where eccentric LVH is subdivided into “indeterminate hypertrophy” and “dilated hypertrophy” and concentric LVH into “thick hypertrophy” and “both thick and dilated hypertrophy.” Compared with participants without LVH, those with dilated, thick, and both thick and dilated hypertrophy were at increased risk for heart failure or CV death after multivariable adjustment, whereas the group with indeterminate hypertrophy was not. In the general population, the 4-tiered classification system for LVH stratified LVH into subgroups with differential risk of adverse CV outcomes.